Effect of Fins on Charging Performance – Release of a PCM-Based Thermal Energy Operating Simultaneously - Musthofa, M. Abdul; Budhi M. Suyitno (Magister Teknik Mesin Universitas Pancasila, 2025)
The use of organic phase change materials (PCMs) has been widely applied as a filling material for thermal energy storage units (TES) due to its relatively low cost, easy availability, and stable temperature during phase change. However, on the other hand, phase change materials have low thermal conductivity, which results in slow operation duration, considered as a drawback. To address this issue, the use of fins inserted into the PCM in a simultaneously operating TES unit is proposed. The effects of flat and pipe aluminum fins were observed in a TES unit using palmitic acid (PA) and myristic acid (MA) as PCMs, resulting in four experimental variations: palmitic acid - flat aluminum fins (PA1), palmitic acid - pipe aluminum fins (PA2), myristic acid - flat aluminum fins (MA1), and myristic acid - pipe aluminum fins (MA2). These variations were tested from ambient temperature up to the PCM temperature of 90°C and back to ambient temperature. The results showed that visually, PCM melts and freezes earlier in the areas near the fins. Based on the experimental data, PA1 was 4.5% faster than PA2, and MA1 was 8.1% faster than MA2 in terms of TES operation duration. Therefore, it can be concluded that the use of flat aluminum fins makes the operation duration faster compared to pipe aluminum fins. The simultaneous operating system caused the exhaust temperature to increase by an average of 11.1°C during the charging process, while during discharging, the exhaust temperature decreased by an average of 14.5°C across the entire TES unit.